Covid-19 Countermeasure Policy in the Province of Jakarta Capital City - Yunita, Irma; Achadi, Anhari; Saputra, Maman; Kusumo, Rangga; Hasani, Nurul; Rusdi, Farhannuddin (Jurnal Kedokteran Brawijaya, 2022)
Jakarta is the highest province of positive Covid-19 cases nationally and the epicenter region in Indonesia. This study aims to analyze the development of the number of cases and Covid-19 countermeasure policy in the Province of Jakarta Capital City. This study uses a qualitative method with in-depth interviews and document review. Primary data was collected from selected informants, namely the Head of Jakarta Health Office and Assistant to the Provincial Secretary for Governmental. Secondary data is taken from legal and policy documents, reports, websites, and press releases. The fluctuation of Covid-19 cases in Jakarta depends on the capacity of the examining laboratory and the capacity of contact tracing. Until April 30, 2020, The Provincial Government of Jakarta Capital City has made 74 policies. They made Covid-19 as a serious policy agenda and collaborates with the whole of government, privates, professional/community/ religious organizations, and society. Situational factors are the most influential factors in the policymaking process. The Provincial Government of Jakarta Capital City concerns early since the Wuhan Pneumonia case with the epidemiological surveillance system of the Health Office, which has been running regularly monitoring infectious diseases from the community health center level. Policy formulation is based on research and scientific studies. Monitoring and evaluation are carried out both formatively and summatively to address problems and obstacles in policy implementation. The Provincial Government of Jakarta Capital City took the early response to collaborates with the whole of government, privates, and society in policymaking and implementation.